SPAC merger announcement returns and subsequent performance. (5th May 2022) - Kiesel, Florian; Klingelhöfer, Nico; Schiereck, Dirk; Vismara, Silvio
Abstract: Special purpose acquisition companies (SPACs) are created to raise capital and then find non‐listed operating companies with which to merge. While most of the extant research has focused on SPAC initial public offerings, we study what happens when SPACs announce business combinations. Our analysis of 236 'deSPACs' completed between January 2012 and June 2021 in the United States documents an average short‐term announcement return of +7.4% and a 1‐year abnormal return of −14.1% (−18.0% over 2 years) for public investors beginning from the merger announcement. Short‐term returns decrease with longer times from initial public offering until announcement.